Ionic liquid with hydrogen bonding reducing leakage charge for enhancing triboelectric performance - Hwang, Hee Jae; Kim, Kyung Yeun; Kim, Joo Sung; Kim, Taeyeon; Kim, Do Hwan; Lee, Younghoon; Choi, Dukhyun (Elsevier BV, 2024)
Refining the dielectric layer of a triboelectric nanogenerator (TENG) has been shown to maximize its output performance. Among the available strategies, utilizing an ionic dielectric can improve the output performance notably through the internal formation of an electrical double layer (EDL). However, ions dispersed in the ionic dielectric inevitably cause leakage charge between the surface charged layer and electrode of the ionic dielectric; this reduces the charge density, directly affecting output performance. Here, we investigate optimization of the ionic dielectric of a TENG using various ionic liquids (ILs), with the alkyl chain lengths of the cations and fluoride of anions with different size, to achieve power enhancement based on the EDL effect while concurrently suppressing leakage charge via hydrogen bonding. To elucidate the power enhancement working mechanisms within the ionic dielectric, we characterize the chemical, mechanical, and electrochemical properties of the ionic dielectric, including formation of hydrogen bonds, ionic conductivity, and dielectric constant. These parameters are investigated by varying the ion types, molecular sizes, and concentrations of the ILs within the ionic dielectric. As a results, our findings reveal that an IL of OMIM+PF & eacute; dissolved in a base material of thermoplastic polyurethane (TPU) significantly enhances the voltage and current by 2.3 and 2.9 times, respectively, compared to those of a conventional TENG with TPU. These findings are expected to be implemented across a wide range of TENGs, paving the path for their advanced applications in next-generation energy harvesting.